Peran Experiential Learning Model Dalam Meningkatkan Kemampuan Pengelolaan Keuangan Rumah Tangga Guru Dan Karyawan SMA Z - Maria Asumpta Evi Marlina; Anastasia Filiana Ismawati; Dwi Sunu Widyo Pebruanto; Lintang Venusita (Jurnal Pendidikan Akuntansi (JPAK), 2021)
This study aims to describe the role of experiential learning models in improving the ability to manage household finances for teachers and employees during the Covid-19 pandemic. This study uses a qualitative descriptive method that is supported by the Wilcoxon signed ranks test different test. Data obtained through interviews, observations, and questionnaires. Qualitative data were obtained during the process of applying the experiential learning model in four stages, namely concrete experience, reflective observation, abstract conceptualization, and active experimentation. Different tests were conducted to show changes in participants' motivation to invest which could indicate changes in the participants' household management abilities. Questionnaires were given to thirty-two respondents who were all participants. The results show that the experiential learning model can improve the ability of teachers and employees of SMA Z in managing their household finances.